1999
DOI: 10.1038/sj.onc.1202977
|View full text |Cite
|
Sign up to set email alerts
|

Human mammary epithelial cells exhibit a differential p53-mediated response following exposure to ionizing radiation or UV light

Abstract: The tumor suppressor protein, p53, plays a critical role as a transcriptional activator of downstream target genes involved in the cellular response to DNA damaging agents. We examined the cell cycle checkpoint response of human mammary epithelial cells (HMEC) and their isogenic ®broblast counterparts to ionizing (IR) and ultraviolet (UV) radiation, two genotoxic agents whose DNA damage response pathways involve p53. Using¯ow cytometric analysis, we found that both mortal and immortalized HMEC, which contain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…All four of our cell lines are wild type for p53 by sequence analysis and express p53 protein (data not shown); therefore, the differences in p21 waf1 expression cannot be attributed to differences in p53 status. p21 waf1 is involved in the G 1 checkpoint response, and others have reported an impaired G 1 checkpoint in HME cell lines (34). Consistent with a strong cell cycle checkpoint in the luminal cell lines, MCF-7 and ZR-75-1 cells also repressed a large set of proliferation genes (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…All four of our cell lines are wild type for p53 by sequence analysis and express p53 protein (data not shown); therefore, the differences in p21 waf1 expression cannot be attributed to differences in p53 status. p21 waf1 is involved in the G 1 checkpoint response, and others have reported an impaired G 1 checkpoint in HME cell lines (34). Consistent with a strong cell cycle checkpoint in the luminal cell lines, MCF-7 and ZR-75-1 cells also repressed a large set of proliferation genes (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…In our cell lines, p53 genes were found to be mutated and the function of p53 was found to be absent in yeast assays. Despite this, we found that the UPN1 exhibited a G2 cell cycle arrest and underwent apoptosis, as this has usually been reported after irradiation (Iavarone and Massague, 1997;Meyer et al, 1999). In our study, UPN2 cell line underwent Sphase arrest after irradiation.…”
Section: Discussionmentioning
confidence: 36%
“…These checkpoints are also activated in response to DNA damage to allow time for repair and to maintain stability of the genome. The importance of p53 in the activation of the G1/S checkpoint after irradiation have been well established (Meyer et al, 1999). This event therefore requires the presence of normal levels of a functional p53 protein, which can then activate its target gene at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…As in many other types of normal human epithelial cells (Flatt et al 1998, Meyer et al 1999, p53 activation by DNA-damaging agents is attenuated in primary cultures of normal prostatic epithelial cells (Girinsky et al 1995, Bromfield et al 2003. This attenuation has been attributed to a need for progenitor or stem-like cells to repress p53 activity so as not to self-eliminate through p53-mediated apoptosis (Dumble et al 2001).…”
Section: Tumor Suppressorsmentioning
confidence: 99%